If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m=(12-3)/(11+1)
We simplify the equation to the form, which is simple to understand
m=(12-3)/(11+1)
Simplifying terms in parentheses
m=(+9)/(11+1)
Simplifying terms in parentheses
m=(+9)/(+12)
Reorder the terms in parentheses
dividing of parentheses
m=( + 0.75)
Remove unnecessary parentheses
m=0.75
We move all terms containing m to the left and all other terms to the right.
+1m=0.75
We simplify left and right side of the equation.
+1m=0.75
We divide both sides of the equation by 1 to get m.
m=0.75
| 9x-1=3+8x | | 275=10(x-50)+75 | | 65=3w-2w^2 | | 3x+7=4x+8 | | 4(3m-10)-6(7m-6)=74 | | f=10(275-50)+75 | | 16=x+15 | | 5+5v=4+5v | | =5m(3m^3-4m)(7m^3-2m^2+5m+1) | | -1(2x-2y)=-1(-4) | | n+19=38 | | -2x+28+6x=42 | | f(2)=8x+3 | | 7+4x=34+4 | | 4+3y=-11 | | 7x+18=25 | | -2(-x-y)=-1(-14) | | 7x+12y=-16 | | 9u-47=2u-4 | | x-3(x+1)=6y-5x | | x^4+4x^2-7=0 | | 1=18+a | | (x+3)(x+5)(x-7)(x-9)=1792 | | 3x=f(w+5)+8 | | (x+3)(x+5)(x-7)(x-9)=0 | | f(w+5)=3x-8 | | 3x-4-5x=-3x-2 | | 36=14x-13x+8 | | 8-x=2x+8 | | 15x=-60 | | 7x-1=7(x+6) | | 2x-y-z=5 |